Covered stents versus balloon angioplasty for failure of arteriovenous access: a systematic review and meta-analysis. Issue 6 (9th June 2021) - Ng, Benjamin; Fugger, Magnus; Onakpoya, Igho Jovwoke; Macdonald, Andrew; Heneghan, Carl
Abstract : Introduction: Patients with end-stage renal disease may require arteriovenous (AV) access in the form of arteriovenous fistulae (AVFs) or arteriovenous grafts (AVGs) for haemodialysis. AV access dysfunction requires intervention such as plain balloon angioplasty or covered stents to regain patency. Aim: To systematically review and meta-analyse the patency outcomes of covered stents in failing haemodialysis AV access, compared with balloon angioplasty. Methods: The review was first registered on the International Prospective Register of Systematic Reviews (CRD42018069955) before data collection. We searched six electronic databases to identify relevant randomised controlled trials (RCTs) up until August 2020, without language restriction. Two reviewers assessed the suitability and quality of studies for inclusion using the Consolidated Standards of Reporting Trials guidelines. We meta-analysed data using a random-effects model. Results: We included seven studies including 1147 patients in the systematic review, of which 867 had AVGs and 280 had AVFs. One study was an ongoing RCT. In the meta-analyses, we assessed patients with failing AVGs only. Overall risk of bias was moderate. Covered stents were associated with lower loss of patency versus angioplasty alone at 6, 12 and 24 months (OR 4.48, 95% CI 1.98 to 10.14, p<0.001; OR 4.07, 95% CI 1.74 to 9.54, p=0.001; OR 2.24, 95% CI 1.17 to 4.29, p=0.01, respectively). Covered stents afforded superior access circuit primary patency compared with angioplasty alone at 6 and 12 months (OR 1.91, 95% CI 1.31 to 2.80, p<0.001; OR 1.97, 95% CI 1.14 to 3.41, p=0.02, respectively). This was not significant at 24 months. There was no significant difference in loss of secondary patency between groups at 12 or 24 months (OR 0.74, 95% CI 0.45 to 1.23, p=0.25; OR 0.67, 95% CI 0.29 to 0.154, p=0.34, respectively). Conclusion: Our results support use of covered stents over angioplasty alone, at 6, 12 and 24 months in failing AVGs. Further clinical trials are warranted.